Міжнародні торгові зв’язки населення Північної Буковини в ХІІ – першій половині ХІІІ ст. - Возний, Ігор (Харків: Майдан; Київ: Стародавній світ, 2017)
I.P. Vozny The In ternational T rade Relations of the P opulation of Northern Bukovina in 12th —the F irst H alf of 13th centuries The population of the Northern Bukovina was engaged in active trade activities with both near and far abroad. The trade was facilitated by the presence of a well-developed network of the international land and waterways. Imported goods, that were found in the researched areas, can be divided into two categories. The first category was represented by the items of the mass import — the coin silver, some types of fabric, kauri seashells. They are the most showing for the researching of the economic relations. The second one — the luxury items — a silver and bronze utensils, a jewelry, a glazed utensil, some gold-weaved silk fabrics. There were well established trade links between the Galician lands, Poland and Hungary. From the last one, were transported some horses, a copper, a silver, a gold and a jewelry. The coin treasures were discovered on the territory of the region and the window glass which were related to Hungary. From Poland were coming a cloth, a wool, a fur, weapons and a tin. There are typical finds of the material culture of the Western Slavs on the territory of Bukovina. This is weapon, a jewelry, etc. There are artefacts that show the connections of the local population with the Baltic states. There were the actively connections of the population of Bukovina with the Northern Black Sea region and Byzantium. This was promoted by the Dniester route, as one of the segments of the «From Varangian to Greeks» route. There were imported articles of Byzantine artistic crafts, small stone sculpture, items of the Christian attributes and the imported containers on the investigated territory. The links with distant areas of Asia can be evidenced by the finds of the kauri shellfish which are originated from the Indian cean, the lazuryt anthropomorphic amulet; the jewelry fabricated from the mountain crystal. Consequently, it is clear from the foregoing, that the territory of the Northern Bukovina, which was situated on the crossing of numerous trade routes, played a role in the development of the international trade.
Keywords: trade; imports; jewelry; amphorae; trade route; coin treasure; import goods; export goods